(Dis)locating Democratization: Music Technologies in Practice. Issue 1 (1st January 2022) - Harkins, Paul; Prior, Nick
ABSTRACT: This article examines the concept of democratization and explains why it has been applied in unhelpful ways to the study of music. We focus on three examples to illustrate the real-world complexities involved in the adoption of new technologies that are often seen as democratic by dint of their widespread use. We argue for a close-reading of the participatory practices of socially-located actors with music-making devices – one that asks detailed questions about who is participating, how, and under what socio-economic conditions. We finish with a call to move beyond the term democratization to an application that is specific to the field of popular music.